APPLYING STUDENT TALKING TIME (STT) IN COMMUNICATIVE ACTIVITY TO IMPROVE THE STUDENTS’ SPEAKING SKILL AT PESANTREN PUTRI AL-MANAWWARAH PANYILI - Dj, MUHAMMAD ZUHRI; ASMAYANTI, ASMAYANTI (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2017)
This research presents research about Applying Student Talking Time Method in Communicative Activity to Improve the Students’ speaking skill at Pesantren Putri Al-Manawwarah Panyili. The objectives of the research are: 1) to know wether Student Talking Time improve the students’ speaking skill of pesantren putri Al-Manawwarah. 2) To know the use of Student Talking Time interested in teaching speaking of the second grade student of SMA Pesantren Putri Al-Manawwarah Panyili. This research used quantitative method. The result of the study shown that there was a significant improvement of the students’ skill after giving the treatment. From the data, it could be conclude that teaching speaking by applying Student Talking Time method in communicative activity is effective to improve students speaking skill and improve students’ motivation in studying speaking.